Hydrodynamic Analysis of Patrol Vessel Based On Seakeeping and Resistance Performance - Firdaus, Nurman; Ali, Baharuddin (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
The patrol vessel must have a good performance criteria for a sea worthiness.The hydrodynamic aspects analysis of a ship design is a main step conduct by designer. This study describes an analysis of motions and ship resistance. The seakeeping test conducted two variations of a ship loading condition. The ship's motion response to sea-state 4 waves with the heading of 180 and 135 deg. The ship resistance test with two draft conditions is calculated by model test and numerical simulation. The ship motion response is expressed in terms of the probability distribution. The values of ship resistance are presented as a non-dimensional graph with a Froude number. The ship loading conditions on a vertical center of gravity is higher resulting in a larger ship motion response than lower vertical center of gravity, as well as the heading of wave is very influential. The results of resistance test above Froude number 0.3, a resistance of ship increase and began to appear hump resistance around a hull.